Risk Factors of Acne Vulgaris among Mosul University Students from Iraq (Iraqi Journal of Medical Sciences, 2022)
Background: Acne vulgaris is a common skin disease, which is a significant health problem among adolescents and young adults. It affects 85-100% of people at some point in their lives, and it usually begins at puberty. Acne can persist into the 30s and beyond.Objective: To evaluate the risk factors for development of acne vulgaris among Mosul University students in Mosul- Iraq.Methods: A case-control study conducted to 300 persons (150 cases and 150 controls) aged 18-35 years selected randomly among Mosul University students who attended university primary health care that located inside Mosul University, Iraq, during the sixth month period from august 2019 to January 2020.Results: Of the acne vulgaris cases (150 cases) that included in the study, 45 % are males and 55% are females, those with age group 18-23 years has 1.8 risk for developing of acne, always stress has 2.7 risk, female cases with irregular cycle have 58 times risk. 53% of female & 46% of male have acne on their face and male patients have 35 risk for acne on their shoulder, oily skin has 3 times risk, two and more members in family with acne have 4 risk followed by 3 times risk of one family member with acne, student’s mobile use has about 2 times risk for developing of acne. Conclusion: There were several significant factors associated with acne formation in the study, which play a role in acne formation including age, psychological status, menstrual cycle irregularity, site of appearance of acne, nature of the skin, family history, using student's mobile.Keywords: Acne vulgaris, risk factors, university studentsCitation: Khaleel FF. Risk factors of acne vulgaris among Mosul University Students from Iraq. Iraqi JMS. 2022; 20(1): 51-58. doi: 10.22578/IJMS.20.1.7
Keywords: Acne vulgaris; risk factors; university students